Transforming Government and Empowering Communities : The Sri Lankan Experience with e-Development - Hanna, Nagy K. (Washington, DC : World Bank, 2012)
This book focuses on the institutional innovations needed to lead the diffusion of the new information and communication technology (ICT) that can help transform developing economies into knowledge economies and information societies. It shows that developing e-leadership institutions is a long-term process, fraught with uncertainties, but a process that remains at the heart of implementing ICT-enabled development strategies. It focuses on improving governance and the delivery of public services, bridging economic divides, promoting social inclusion, and drastically cutting transaction costs across the economy. It seeks to exploit new sources of growth, employment, and competitiveness by promoting the ICT and IT-enabled services industries and the use of ICT by small enterprises to network and compete. This book draws on the experience of Sri Lanka to explore what is involved in moving from vision to implementation of a comprehensive e-development strategy-the e-Sri Lanka program. The focus is on building local e-leadership institutions to drive this process and leveraging ICT to transform government and empower communities through e-government and e-society. Finally, to allow sound selection and management of projects, particularly in a national context, it is critical that the program be free from pressure by government, private companies, or others that may seek to use the program to exercise their influence.